2ND-HARMONIC RESONANCE IN NONCONSERVATIVE SYSTEMS - Craik, A; Nagata, M; Moroz, I (1992)
The amplitude equations of second-harmonic resonance are studied, for wave amplitudes that exhibit both spatial and temporal variation. We emphasise cases subject to linear growth or damping and also to non-conservative quadratic interactions characterised by complex coupling coefficients. Classes of separable solutions and 'propagating' solutions of permanent form are described and connections are made with previous work. It is found that many, but not all, solutions exhibit singularities. © 1992.